Energy modelling in architecture : a practice guide - Oliviera, Sonja; Marco, E. (Elena); Gething, Bill (London : RIBA Publishing Ltd., 2020)
This book offers a practical guide to embedding energy modelling in architectural practice. With expert contributions from leading architects and practices, this book illustrates architects' approaches to learning, sharing and integrating energy modelling across a range of design projects, in both small and large firms in the UK and internationally. Discussing the practical and business implications of embedding energy modelling in practice, this is an essential manual for the energy-literate architect.
OCLC-licensed vendor bibliographic record.
Keywords: Architecture and energy conservation; ARCHITECTURE / General